2011
DOI: 10.1017/s1759078711001000
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic dosimetry for adult and child models within a car: multi-exposure scenarios

Abstract: International audienceThis paper deals with the numerical dosimetry for adult and children models exposed to CW signals of several wireless communication systems (UMTS, WiMax, and Bluetooth) within a partly shielded environment represented by a realistic car model. More than 20 mono-and multi-source exposure scenarios are considered. Computational results demonstrate that, for all considered exposure scenarios, the specific absorption rate (SAR) is at least 40 times (whole-body average) and 10 times (local SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Some studies focused on the assessment of the RF-EMF exposure inside road vehicles by using computational methods [66,67,68]. In the study by Harris and colleagues [66] numerical dosimetry for adult and children models exposed to several wireless communication systems (UMTS, WiMax, and Bluetooth) localized in different positions within a partly shielded environment represented by a realistic car model, considering different exposure scenarios. Results showed that for a single operating device, the maximum whole body SAR for adults and for children exposure is 1.39 and 1.58 mW/kg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies focused on the assessment of the RF-EMF exposure inside road vehicles by using computational methods [66,67,68]. In the study by Harris and colleagues [66] numerical dosimetry for adult and children models exposed to several wireless communication systems (UMTS, WiMax, and Bluetooth) localized in different positions within a partly shielded environment represented by a realistic car model, considering different exposure scenarios. Results showed that for a single operating device, the maximum whole body SAR for adults and for children exposure is 1.39 and 1.58 mW/kg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This cell size takes into consideration the computer resources that would be required for the numerical simulation. We determine the dielectric properties of the human body by "two-thirds muscle" approximation at the operating frequency (Harris et al, 2011). The relative permittivity and conductivity of the human model, which are taken from the IFAC tissue database according to the operating frequency of the system, are 8,312 and 0.2316 S/m, respectively (Gabriel et al, 1996).…”
Section: Models and Methodsmentioning
confidence: 99%
“…The consequent models are of two refinements, homogeneous and inhomogeneous. For the first ones, the dielectric belongings are generally endorsed to a 2/3 equivalent muscle model [90]. For inhomogeneous models, ghost models of layered stuff are built on magnetic resonance imaging (MRI), computed tomography and arithmetic imaging techniques, offering exactness of tissue profile to the nearest millimeter [91,92].…”
Section: Human Body Modelmentioning
confidence: 99%